Cord injury after spinal anaesthesia in a patient with previously undiagnosed Klippel–Feil syndrome. Issue 1 (11th March 2019) - Stevens, E.; Williams, B.; Kock, N.; Kitching, M.; Simpson, M. P.
Summary: This report presents an obstetric patient with no significant past medical history who underwent spinal anaesthesia for a category‐three caesarean section. On examination, she had asymmetrical scapular alignment and a mild scoliosis of the lumbar spine with no functional limitation. Postoperatively the patient developed neuropathic pain symptoms in the right leg which failed to resolve with conventional analgesia. Cervical and lumbar spine magnetic resonance imaging was performed resulting in a diagnosis of a low‐lying tethered spinal cord terminating at the level of L5 and congenital fusion of the C7/T1 vertebrae. A tethered spinal cord is a rare condition, which in this case had been completely asymptomatic. However, we suggest that the patient displayed musculoskeletal signs not previously widely reported, which could have indicated the presence of a potential underlying neural tube defect. Based on the imaging findings and the presence of Sprengel's deformity, the patient was diagnosed with Klippel–Feil syndrome.